2011
DOI: 10.4315/0362-028x.jfp-10-520
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Antimicrobial Coatings on the Radiosensitization of Escherichia coli, Salmonella Typhimurium, and Listeria monocytogenes in Fresh Broccoli

Abstract: Radiosensitization of Listeria monocytogenes, Escherichia coli, Salmonella Typhimurium, and aerobic microflora was evaluated in broccoli florets coated by antimicrobial coatings and treated with different doses of γ-radiation. Broccoli florets were inoculated with aerobic microflora isolated from broccoli and with pathogenic bacteria (L. monocytogenes, E. coli, and Salmonella Typhimurium) at 10(6) CFU/ml. Inoculated florets were then coated with methylcellulose-based coating containing various mixtures of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The obtained results with gamma irradiation treatments showed that L. monocytogenes was more resistant to gamma irradiation than E. coli O157:H7, which is consistent with several previous studies (Takala et al, 2011;Yun et al, 2011). Cauliflower samples treated with gamma rays showed the best visual quality among all samples (data not shown), indicating that this type of treatment had a very negligible impact on vegetables.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The obtained results with gamma irradiation treatments showed that L. monocytogenes was more resistant to gamma irradiation than E. coli O157:H7, which is consistent with several previous studies (Takala et al, 2011;Yun et al, 2011). Cauliflower samples treated with gamma rays showed the best visual quality among all samples (data not shown), indicating that this type of treatment had a very negligible impact on vegetables.…”
Section: Resultssupporting
confidence: 94%
“…These results indicated that application of irradiation treatment after applying natural antimicrobial formulations, could have the antimicrobial effect in short term, as shown by several studies (Takala et al, 2011;Turgis et al, 2011;Yun et al, 2011), but the long-term antimicrobial effect might be diminished. Therefore, spraying of natural antimicrobial formulations on products, followed by the irradiation (UV-C or gamma) treatment on products, prevents interferences between these two methods.…”
Section: Tablementioning
confidence: 67%
See 1 more Smart Citation
“…The molecular characterization revealed the interaction between alginate-CNC and nisin which also demonstrated the better retention activity of microencapsulated nisin during storage. The radiosensitization of L. monocytogens, Escherichia coli, S. Typhimurium and aerobic microflora in broccoli florets coated by antimicrobial coatings immobilized in methylcellulosebased coating was evaluated by Takala et al [69]. The coating contained different mixtures of antimicrobial agents such as organic acids/lactic acid bacteria (LAB metabolites), organic acids/citrus extract, organic acids/citrus extract/spice mixture and organic acids/rosemary extract, and coated florets were treated with different doses of γ-irradiation.…”
Section: Combination With Edible Coating and Encapsulationmentioning
confidence: 99%
“…Several authors in previous works on γ‐irradiation treatment combined with other nonthermal treatments reported that the survival microorganisms after irradiation treatment are more sensitive to nonthermal treatments than untreated cells to adverse environmental conditions, such as in the presence of antimicrobial compounds or modified atmosphere (Severino and others , 2015). Takala and others () showed the antimicrobial effect of coatings containing citrus and rosemary extracts, spice mixture, and lactic acid increases the radiosensitization of E. coli, S . Typhimurium, and L. monocytogenes in broccoli florets.…”
Section: Introductionmentioning
confidence: 99%